Assistance In Editing a Bilingual Dictionary (Indonesia-Ciacia): Pendampingan Penyuntingan Kamus Dwibahasa (INDONESIA-CIACIA) - Arimi, Sailal; Uniawati; Hanafi, Muhammad; Nur, Andi Herlina; Nofrianto, Noke; Huzaena, Mifta; Ghazali, Fikri; Azim, Nur Santriani Utari; Nurwulan, Zulhilda; Fatonah, Astri Amaliah; Mailawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The emergency of language death is something that must be anticipated, one of the ways that can be taken to protect the language is by compiling a dictionary of the language (language documentation and revitalization). This study aims to support the preservation of the Cia-Cia language, a regional language of Southeast Sulawesi that is endangered. The UGM Master of Linguistics study program community service team collaborates with the Officers of Southeast Sulawesi language Institution compiled a bilingual Indonesian-Cia-Cia dictionary. The assistance provided is by holding workshops involving lexicography experts, students, and native speakers of the Cia-Cia language over a period of six months. The method was carried out online through a step-by-step procedure, including the planning, implementation, and evaluation stages. The result of the study is a bilingual Indonesian–Cia-Cia Dictionary containing 2,000 entries. It is hoped that this activity will serve as an initial step in the ongoing efforts to document and revitalize the Cia-Cia language in the future.